Role of Na+/H+ Exchanger Isoform-1 in Human Inflammatory Bowel Disease - Islam Khan; Iqbal Siddique; Farida M Al-Awadi; Krishna Mohan (Canadian Journal of Gastroenterology)
BACKGROUND: Na+/H+ exchanger (NHE) is responsible for a net uptake of sodium chloride and water from the gastrointestinal tract and maintains electrolyte and water homeostasis. However, its status in human inflammatory bowel disease such as ulcerative colitis (UC) and Crohn’s disease (CD) remains poorly understood.